1998
DOI: 10.1063/1.368136
|View full text |Cite
|
Sign up to set email alerts
|

Time- and temperature-dependent wetting behavior of eutectic SnPb on Cu leadframes plated with Pd/Ni and Au/Pd/Ni thin films

Abstract: We have studied the wetting behaviors of eutectic SnPb solder on Cu leadframes plated with Pd/Ni and Au/Pd/Ni thin films. For the Pd/Ni, we used two thicknesses of Pd of 760 and 2500 Å to study the thicknesses effect. For the Au/Pd/Ni, we used either immersion Au (50 Å) or acid Au (50 Å) flashed on 1000 Å Pd to study the effect and method of adding Au to the Pd surface. In addition, we investigated the wetting on a PdSn3 compound surface made by plating Sn or eutectic SnPb on Pd/Ni samples and then stripping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…16 After the Au disappeared from the interface, the underlying metallization layer, i.e., the Pd(P) layer, was exposed. The soldering reaction of Pd is just as complicated as that of Au, 14,15 but only PdSn 4 is depicted in Fig. 9 for brevity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…16 After the Au disappeared from the interface, the underlying metallization layer, i.e., the Pd(P) layer, was exposed. The soldering reaction of Pd is just as complicated as that of Au, 14,15 but only PdSn 4 is depicted in Fig. 9 for brevity.…”
Section: Discussionmentioning
confidence: 98%
“…The depletion process of Pd in the molten solder is similar to that of Au in two ways. First, the Pd would be quickly converted into PdSn 4 [or (Pd,Ni)Sn 4 ], [14][15][16] which has a similar crystal structure to AuSn 4 . 33 Additionally, this compound would break from the root of grains and then separate from the interface during soldering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, surface Au/Pd finishes can be removed very quickly through dissolution/reaction when they contact a molten solder. [13][14][15] It was found that, immediately after the topmost Au is removed, the Pd of the Pd(P) layer converts into the PdSn 4 [or (Pd,Ni)Sn 4 ] phase, which in turn spalls into the molten solder. 15 The remaining P further reacts with Ni and Sn and crystallizes into the Ni 2 SnP phase.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The Pd film is customarily deposited within a thickness range of 0.05 lmÀ0.3 lm 1,6 and can quickly alloy with molten solder at an early stage of soldering. [7][8][9] Removal of the Pd exposes the underlying Ni(P) to the solder, which might contain various Pd concentrations. The Pd concentration in the solder varies as a function of joint size and Pd thickness.…”
Section: Introductionmentioning
confidence: 99%